Knowledge and self-perceived competence about cardiopulmonary resuscitation among youths: a cross-sectional study in a sample of Italian undergraduates - Protano, Carmela; Cammalleri, Vittoria; Zanni, Stefano; Valeriani, Federica; Liguori, Giorgio; Spica, Vincenzo Romano; Vitali, Matteo; Gallè, Francesca (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Cardiopulmonary resuscitation is fundamental to improve the outcomes of a life-threatening event. The correct knowledge of first aid actions to provide may guarantee the victim’s survival. This study was aimed at evaluating the competence about cardiopulmonary resuscitation and its predictors in a sample of Italian undergraduate students. Methods. Information on socio-demographic characteristics, first aid training, knowledge of stroke and heart attack symptoms and perceived ability to provide first aid, were collected through a web-based questionnaire. Results. On a total of 744 respondents (mean age 23.9±5.4 years, 62.5% female), 71.4% identified correctly first aid actions, 59.9% and 60.8% showed a good knowledge of stroke and heart attack symptoms, respectively. However, only 39.0% of them declared their ability to intervene in case of emergency. Attending a healthcare degree course and having had first aid training were associated with knowledge of symptoms and perceived ability to provide first aid. Female gender was negatively related with perceived ability to intervene. Conclusions. In spite of the satisfactory level of knowledge, these findings highlight the need to enhance the competence about cardiopulmonary resuscitation in the lay population, especially among females.